Pengujian Performa Pompa Air DAB Tipe DB-125B Sebagai Turbin - Verdy A. Koehuan; Gusnawati Gusnawati; Phillips G. Taka Logo (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2021)
A centrifugal pump is a pump that moves fluid by utilizing the centrifugal force generated by the rotation of the impeller. All rotodynamic pumps from radial flow type to axial flow can function as turbines. The research was conducted through experiments on the pump that functions as a turbine in this study is a regenerative pump or peripheral pump, namely water pump DAB type DB-125B. Peripheral pump is a centrifugal pump whose impeller has radial spoons in a total of 41 spoons. The results showed the best performance or performance of PAT regenerative pump system or peripheral pump, namely water pump DAB type DB-125B as a hydro power plant with flow discharge variation of 35 ltr/min, 40 ltr/min, and 45 ltr/min at constant head (8 m) is with a maximum efficiency of 15.81% at a flow discharge of 40 ltr/min and shaft rotation of 850.3 rpm. Maximum PAT output power also occurs at a flow discharge of 40 ltr/min with a turbine rotation of 985.1 rpm of 5.849 W. The addition of water power can directly increase the rotation of the PAT shaft, as well as the addition of flow discharge at a constant head (8 m), rotation the turbine rotor is also increased. Whereas the addition of flow discharge with a constant head, the output power and maximum PAT efficiency tend to occur at high rotation.